A Nucleus-Encoded Chloroplast Phosphoprotein GovernsExpression of the Photosystem I Subunit PsaC inChlamydomonas reinhardtii - Douchi, Damien; Qu, Yujiao; Legendre-Lefebvre, Linnka; Johnson, Xenie; Schmitz-Linneweber, Christian; Goldschmidt-Clermont, Michel (My University, 2016)
The nucleo-cytoplasmic compartment exerts anterograde control on chloroplast gene expression through numerous proteinsthat intervene at posttranscriptional steps. Here, we show that thematuration of psaCmutant (mac1)ofChlamydomonasreinhardtiiis defective in photosystem I and fails to accumulatepsaCmRNA. TheMAC1locus encodes a member of the Half-A-Tetratricopeptide (HAT) family of super-helical repeat proteins, some of which are involved in RNA transactions. The Mac1protein localizes to the chloroplast in the soluble fraction.MAC1acts through the 59untranslated region ofpsaCtranscriptsand is required for their stability. Small RNAs that map to the 59end ofpsaCRNA in the wild type but not in themac1mutantare inferred to represent footprints ofMAC1-dependent protein binding, and Mac1 expressed in bacteria binds RNA in vitro. Acoordinate response to iron deficiency, which leads to dismantling of the photosynthetic electron transfer chain and inparticular of photosystem I, also causes a decrease of Mac1. Overexpression of Mac1 leads to a parallel increase inpsaCmRNA but not in PsaC protein, suggesting that Mac1 may be limiting forpsaCmRNA accumulation but that other processesregulate protein accumulation. Furthermore, Mac 1 is differentially phosphorylated in response to iron availability and toconditions that alter the redox balance of the electron transfer chain